The Bologna Process' impact on cross-national student mobility: A multi-method evaluation - Eva Maria Voegtle; Timm Fulge (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2013)
The Bologna Process (BP) has induced a remarkable amount of structural higher education policy change in its participating countries. From a program-theoretical perspective, one of the main benefits associated with these changes is thought to be increased student mobility between participating countries. However, due to a lack of suitable data and the highly heterogeneous nature of the newly-formed European Higher Education Area (EHEA), it has thus far remained unclear whether student mobility has indeed increased and, if it has, whether countries benefit evenly. In this paper, we aim to evaluate (1) whether the Bologna Process has led to an increase in degree seeking student mobility within as well as beyond the EHEA and (2) whether the exchange relationships are balanced. Drawing from previous literature on student mobility, we isolate the impact of BP membership from other factors hypothesized to shape mobility flows. Methodologically, we employ a two-fold approach: First, we conduct time-series-crosssection (TSCS) analyses of both in- and outbound degree seeking student mobility ratios, establishing which factors account for the overall attractiveness of higher education systems. Secondly, we take a dyadic approach in order to analyze push and pull factors between pairs of countries. In short, we find that while membership in the Bologna Process does not have an impact on inbound mobility ratios, outbound mobility ratios have indeed increased within the group of BP members. However, although participation in the BP per se does not further inbound mobility or relevance of exchange relationships, cross-national student exchange patterns within this group are more balanced compared to those of non-participants. In conclusion, the BP has failed to establish the EHEA as a favorite destination for degree seeking student mobility. – – Der Bologna-Prozess hat weitreichende hochschulpolitische Veränderungen in den teilnehmenden Ländern hervorgerufen. Ein zentrales Ziel dieser strukturellen Veränderungen war es, studentische Mobilität zwischen den teilnehmenden Ländern zu erhöhen. Aufgrund der unzureichenden Datenlage und der hohen Heterogenität innerhalb des neu gegründeten Europäischen Hochschulraumes bleibt die Frage, ob das Ziel gestiegener Mobilität tatsächlich erreicht worden ist, ungeklärt. Auch ist bisher noch nicht untersucht worden, ob die Mobilitätsmuster zwischen den teilnehmen Ländern - wie durch den Bologna-Prozess angestrebt - ausgeglichener geworden sind. In diesem Arbeitspapier analysieren wir daher, ob der Bologna-Prozess zu einer Zunahme der länderübergreifenden studentischen Mobilität geführt hat und inwiefern diese Austauschprozesse ausgeglichen sind. Unter Rückgriff auf bestehende Literatur zu internationaler studentischer Mobilität isolieren wir den Einfluss des Bologna-Prozesses von anderen Faktoren, die studentische Mobilität prägen. Dabei wird einerseits eine Time-Series-Cross-Section (TSCS) Analyse von aufgenommenen internationalen Studierenden (inbound mobility) als auch ausgehenden nationalen Studierenden (outbound mobility) durchgeführt. Darüber hinaus untersuchen wir anhand des dyadischen Ansatzes welche Faktoren die Attraktivität eines Landes als Studienort im zwischenstaatlichen Vergleich bestimmen. Zusammenfassend können wir feststellen, dass Mitgliedschaft im Bologna-Prozess per se nicht die Attraktivität als Studiendestination für ausländische Studierende erhöht. Jedoch wirkt sich die Teilnahme förderlich auf ausgehende Mobilität aus und die studentischen Austauschprozesse zwischen den Teilnehmern sind ausgeglichener im Vergleich zu den Nicht-Teilnehmenden OECD Ländern. Insgesamt konstatieren wir, dass der Bologna Prozess nicht das Ziel erreicht hat den Europäischen Hochschulraum als bevorzugte Studiendestination für den Abschluss eines gesamten Studienzyklus zu etablieren.
Keywords: 300